Recent advances in radiation-hardened fiber-based technologies for space applications. (1st August 2018) - Girard, Sylvain; Morana, Adriana; Ladaci, Ayoub; Robin, Thierry; Mescia, Luciano; Bonnefois, Jean-Jacques; Boutillier, Mathieu; Mekki, Julien; Paveau, Armelle; Cadier, Benoît; Marin, Emmanuel; Ouerdane, Youcef; et al.
Abstract: In this topical review, the recent progress on radiation-hardened fiber-based technologies is detailed, focusing on examples for space applications. In the first part of the review, we introduce the operational principles of the various fiber-based technologies considered for use in radiation environments: passive optical fibers for data links, diagnostics, active optical fibers for amplifiers and laser sources as well as the different classes of point and distributed fiber sensors: gyroscopes, Bragg gratings, Rayleigh, Raman or Brillouin-based distributed sensors. Second, we describe the state of the art regarding our knowledge of radiation effects on the performance of these devices, from the microscopic effects observed in the amorphous silica glass used to design fiber cores and cladding, to the macroscopic response of fiber-based devices and systems. Third, we present the recent advances regarding the hardening (improvement of the radiation tolerance) of these technologies acting on the material, device or system levels. From the review, the potential of fiber-based technologies for operation in radiation environments is demonstrated and the future challenges to be overcome in the coming years are presented.